Association between cytokines and functional, hemodynamic parameters, and clinical outcomes in pulmonary arterial hypertension - Joshi, Aditya A. (Pulm Circ, 2018)
To assess the relationship of cytokines with functional and clinical outcomes in pulmonary arterial hypertension (PAH). Endothelial dysfunction and vascular inflammation are characteristic of PAH. We investigated whether markers of angiogenesis and inflammation associated with functional, hemodynamic parameters, and clinical outcomes in PAH. PAH patients (n = 206) were pooled from two clinical trials: TRUST-1 and FREEDOM-C2. Baseline and post-treatment cytokine levels were correlated to baseline clinical and hemodynamic parameters, were assessed in clinical subgroups, and were associated with clinical outcomes. In 206 patients (mean age = 48 years; 74% women) with WHO group-1 PAH, most cytokine levels were higher in those with 6-min walking distance (6MWD) < median (335 m) vs. those above median, including Ang-1 (11.9 ± 10.1 vs. 5.9 ± 6.0 ng/mL), Ang-2 (14.3 ± 11.8 vs. 12.2 ± 11.2 ng/mL), and MMP-9 (221 ± 262.3 vs. 119 ± 171 ng/mL). Baseline 6MWD inversely correlated with Ang-1 (r = −0.27, P < 0.0001), Ang-2 (r = −0.20, P = 0.004), and MMP-9 (r = −0.27, P < 0.0001). MMP-9 levels differed significantly by NYHA functional class (P = 0.001) suggesting an association between MMP-9 and subjective PAH severity. Mean Ang-2 levels were higher in those with baseline right atrial pressure (RAP) > 15 mmHg compared to those with RAP < 15 mmHg (23,841 vs. 11,020 pg/mL). Baseline RAP was associated with change in MMP-9 levels (r = −0.53, P = 0.03). Finally, baseline Ang-1, VEGF and MMP-9 levels were associated with risk of death and hospitalization at 16-week follow-up. Inflammatory cytokines and vascular angiogenesis markers are associated with baseline functional, hemodynamic parameters in PAH, and predict death and hospitalization. Larger prospective studies are needed to confirm the utility of cytokines in PAH.